2019
DOI: 10.4103/jmss.jmss_25_18
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the radiosensitizing potency of bromelain for radiation therapy of 4T1 breast cancer cells

Abstract: Breast cancer (BC) remains the leading cause of death in women worldwide, despite the improvements of cancer screening and treatment methods. Recently, development of novel anticancer drugs for the improved prevention and treatment of BC is in the center of research. The anticancer effects of bromelain, as enzyme extract derived from the pineapples, contains chemicals that interfere with the growth of tumor cells. The aim of this study was to evaluate the effect of radiosensitizing of bromelain in 4T1 BC cells… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 28 publications
(37 reference statements)
0
6
0
1
Order By: Relevance
“…The aptitude of bromelain to engage in-vitro human leukemia cell differentiation was already mechanisms reported. Additionnaly, bromelain proved to be of radiosensitizing feature in 4T1 mouse breast cancer cell line [ 14 ]. In the current study, single-agent bromelain or cisplatin treatment displayed a significant dose and time-dependent effect on inhibition of PC3 cell proliferation at three different incubation times of 24, 48 and 72 hours ( Figure-1 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The aptitude of bromelain to engage in-vitro human leukemia cell differentiation was already mechanisms reported. Additionnaly, bromelain proved to be of radiosensitizing feature in 4T1 mouse breast cancer cell line [ 14 ]. In the current study, single-agent bromelain or cisplatin treatment displayed a significant dose and time-dependent effect on inhibition of PC3 cell proliferation at three different incubation times of 24, 48 and 72 hours ( Figure-1 ).…”
Section: Discussionmentioning
confidence: 99%
“…Cell culture efficiency was measured by the formula [yield efficiency=(number of colonies formed / number of cultured cells) × 100]. The survival ratio for treatment groups was calculated using the formula [survival ratio=(efficiency of cultures with treatment / efficiency of cultures without treatment) × 100) [ 14 ].…”
Section: Methodsmentioning
confidence: 99%
“…The radioresistance of MCF-7 breast carcinoma cells was mention before in the study of Jänicke et al 43 Previous reports showed that the in vitro treatment of tumor cell lines with BL results in inhibition of cell growth and invasion capacities. 26 , 44 , 45 It has been reported that BL has a tumoricidal activity in vitro via induction of ROS and subsequent mitochondrial membrane depolarization, later on leading to oxidative stress as well as through its autophagy action. 46 , 47 The anticancer effect of BL has been credited mainly to its protease component through digestion and diffusion in tumor cells.…”
Section: Discussionmentioning
confidence: 99%
“…Cell culture efficiency was measured by the formula [yield efficien-cy=(number of colonies formed / number of cultured cells) × 100]. The survival ratio for treatment groups was calculated using the formula [survival ratio=(efficiency of cultures with treatment / efficiency of cultures without treatment) × 100) [14].…”
Section: Mtt Assay To Appraisal Cell Proliferation Inhibitory Effectmentioning
confidence: 99%